For the point 19, we need to note that the function g(x) is the function f(x) moved 2 units to the left in the x-axis and moved 4 units upward in the y-axis, then we need to return this transformation to get back to f(x), then what we need to do is to move the graph two units to the right and 4 units down, and the result will be:
For the point 20, what we are going to do is to look at each of the points and transform them to the preimage. for example:
since g(-3)=2 then 2f(-3-3)-2=2 then f(-6)=2
since g(-2)=4 then 2f(-2-3)-2=4 then f(-5)=3
since g(0)=1 then 2f(0-3)-2=1 then f(-3)=1.5
since g(1)=3 then 2f(1-3)-2=3 then f(-2)=2.5
since g(3)=3 then 2f(3-3)-2=3 then f(0)=2.5
now we can graph these points to obtain the new graph:
For the point 21:
since g(-3)=2 then 1/2f(-(-3))-4=2 then f(3)=12
since g(-2)=4 then 1/2f(2)-4=4 then f(2)=16
since g(0)=1 then 1/2f(0)-4=1 then f(0)=10
since g(1)=3 then 1/2f(-1)-4=3 then f(-1)=14
since g(3)=3 then f(-3)=14... and now we can do the third graph: